2022
DOI: 10.3390/ma15030958
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Technique Diagnostic Analysis of Plasters and Mortars from the Church of the Annunciation (Tortorici, Sicily)

Abstract: Plasters and mortars of the Church of the Annunciation (Tortorici, Sicily) were characterized, for the first time, both at the elemental and molecular levels, by means of portable X-ray fluorescence (XRF) and Raman spectroscopy, to achieve information on the “state of health” of the whole structure. The understanding of their degradation mechanisms and the identification of consequent degradation patterns can define the environmental factors responsible for interpreting the potential pathological forms that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…SEM-EDS may be replaced by automated instrumental systems, such as the QuemSCAN [90], which is very useful for identifying and quantifying the mineral composition of samples limiting the operator's influence on the interpretation. Unusual anthropogenic components, such as brick, and mortar [91], paper, plastic and glass fragments, or paint slices found in the geological physical evidence, maybe also characterized using X-ray fluorescence XRF and RAMAN spectroscopy. Attendees analyze some paint slices by XRF (Figure 19).…”
Section: Laboratory Experience On Geological Physical Evidence Color-...mentioning
confidence: 99%
See 1 more Smart Citation
“…SEM-EDS may be replaced by automated instrumental systems, such as the QuemSCAN [90], which is very useful for identifying and quantifying the mineral composition of samples limiting the operator's influence on the interpretation. Unusual anthropogenic components, such as brick, and mortar [91], paper, plastic and glass fragments, or paint slices found in the geological physical evidence, maybe also characterized using X-ray fluorescence XRF and RAMAN spectroscopy. Attendees analyze some paint slices by XRF (Figure 19).…”
Section: Laboratory Experience On Geological Physical Evidence Color-...mentioning
confidence: 99%
“…Attendees analyze some paint slices by XRF (Figure 19). Unusual anthropogenic components, such as brick, and mortar [91], paper, plastic and glass fragments, or paint slices found in the geological physical evidence, maybe also characterized using X-ray fluorescence XRF and RAMAN spectroscopy. Attendees analyze some paint slices by XRF (Figure 19).…”
Section: Laboratory Experience On Geological Physical Evidence Color-...mentioning
confidence: 99%
“…The similarities among Raman spectra taken at "A", "B", and "C" strongly suggested that those three types of crystals clusters shared the same mineral composition. Weak C peaks around 1360 and 1580 cm −1 would appear if amorphous carbon existed in the glaze [37,38]. Besides these observations, we measured the phase constituent of the underlying black glaze (Figure 5b); due to its amorphous nature, the received spectrum showed obvious, glassy peaks (458 cm −1 and 976 cm −1 are the typical envelope peaks of glass [25]).…”
Section: Phase Analysis By Xrd and Rsmentioning
confidence: 99%
“…Ultramarine was a very expensive and precious blue pigment extensively used in Europe throughout medieval paintings [3]. This precious pigment took on an iconographic value, and it was reserved for the robes of only the most prominent figures, such as Christ and the Virgin Mary, in religious scenes [3,6]. In 1828, a synthetic version of the ultramarine blue pigment was first obtained using a chemical process involving both calcination and oxidation steps [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, μ-Raman spectroscopy was chosen in this study due to its exceptional ability to predict and discover the compositional properties of inorganic materials (e.g., crystalline phases and their transitions), as well as of organic materials or functional groups. The peculiarity of this technique consists in its non-destructive and repeatability character and its high sensitivity, also for portable instrumentations, a characteristic highly desirable for field tests of precious ancient relics [6].…”
Section: Introductionmentioning
confidence: 99%